Iron accumulation in skeletal muscles of old mice is associated with impaired regeneration after ischaemia–reperfusion damage. Issue 2 (4th March 2021) - Alves, Francesca M.; Kysenius, Kai; Caldow, Marissa K.; Hardee, Justin P.; Crouch, Peter J.; Ayton, Scott; Bush, Ashley I.; Lynch, Gordon S.; Koopman, René
Abstract: Background: Oxidative stress is implicated in the insidious loss of muscle mass and strength that occurs with age. However, few studies have investigated the role of iron, which is elevated during ageing, in age‐related muscle wasting and blunted repair after injury. We hypothesized that iron accumulation leads to membrane lipid peroxidation, muscle wasting, increased susceptibility to injury, and impaired muscle regeneration. Methods: To examine the role of iron in age‐related muscle atrophy, we compared the skeletal muscles of 3‐month‐old with 22‐ to 24‐month‐old 129SvEv FVBM mice. We assessed iron distribution and total elemental iron using laser ablation inductively coupled plasma mass spectrometry and Perls' stain on skeletal muscle cross‐sections. In addition, old mice underwent ischaemia–reperfusion (IR) injury (90 min ischaemia), and muscle regeneration was assessed 14 days after injury. Immunoblotting was used to determine lipid peroxidation (4HNE) and iron‐related proteins. To determine whether muscle iron content can be altered, old mice were treated with deferiprone (DFP) in the drinking water, and we assessed its effects on muscle regeneration after injury. Results: We observed a significant increase in total elemental iron (+43%, P  < 0.05) and lipid peroxidation (4HNE: +76%, P  < 0.05) in tibialis anterior muscles of old mice. Iron was further increased after injury (adult: +81%, old: +135%, P  < 0.05) and associated with increased lipid peroxidation (+41%, P  < 0.05). Administration of DFP did not impact iron or measures of lipid peroxidation in skeletal muscle or modulate muscle mass. Increased muscle iron concentration and lipid peroxidation were associated with less efficient regeneration, evident from the smaller fibres in cross‐sections of tibialis anterior muscles (−24%, P  < 0.05) and an increased percentage of fibres with centralized nuclei (+4124%, P  < 0.05) in muscles of old compared with adult mice. Administration of DFP lowered iron after IR injury (PRE: −32%, P  < 0.05 and POST: −41%, P  < 0.05), but did not translate to structural improvements. Conclusions: Muscles from old mice have increased iron levels, which are associated with increased lipid peroxidation, increased susceptibility to IR injury, and impaired muscle regeneration. Our results suggest that iron is involved in effective muscle regeneration, highlighting the importance of iron homeostasis in muscle atrophy and muscle repair.